System edukacji jako czynnik konkurencyjności gospodarek Unii Europejskiej - Dobrzański, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The main goal of the article is to present that today education is one of the key elements affecting the international competitiveness. For this purpose the paper defines and presents the relationship between international competitiveness and human capital that is created by education systems. The paper also discusses the impact of education on the competitiveness of economies and the education policy of the European Union. Last part of the paper presents quantitative measurement methods of education used by the European Union – “European Innovation Scoreboard”. Then, indicators characterizing education as an element of competitiveness are analyzed in detail.
Keywords: konkurencyjność; innowacje; system edukacji; wzrost gospodarczy